Adverse reactions by antibiotics and non-steroidal anti-inflammatory drugs - Karen Orellana; Alejandro Carías; Wendy Cruz; Fredy Rodriguez Rivas; David Naira; Perla Simons Morales (GarVal Editorial Ltda., 2022)
Context: Adverse drug reactions represent one of the leading causes of hospitalization and death. Aims: To characterize adverse reactions due to antibiotics and nonsteroidal anti-inflammatory drugs in outpatients over 18 years of age. Methods: Cross-sectional descriptive observational study. It included outpatients aged 18 years or older who went to public health care centers and who presented a health problem, for which they were treated with antibiotics or nonsteroidal anti-inflammatory drugs (NSAIDs). The information was collected through an adaptation of the adverse drug reaction (ADR) report format in outpatients. Results: A sample of 4,573 participants was obtained, of which 556 (12.4%) people presented adverse drug event, 550 ADR were detected by NSAIDs and antibiotics, of which, 51.4% (291) were classified according to Naranjo's algorithm as probable, 37.8% (214) as possible and 8.0% (45) as defined. According to the Rawlins and Thompson classification the majority were type A with 413 (75.1%). The severity was mostly mild, with 471 (85.6%) and the manifestations of the digestive system predominated with 440 (80.0%). Conclusions: It is necessary to promote and strengthen pharmacovigilance activities, as well as the training and updating of health personnel in the detection of ADR, since in many cases these can be avoided, contributing to patient safety and the reduction of public spending on health, especially in low-income countries.